Cluster headache: state of the art in treatment - Rodriguez-Leyva, Ildefonso; Velez-Jimenez, Maria-Karina; García, Silvia; Nader-Kawachi, Juan Alberto; Martínez-Mayorga, Adriana Patricia; Melo-Carrillo, Agustín; Juárez-Jimenez, Humberto; Martinez-Gurrola, Marco; Gudiño-Castelazo, Manuel; Chiquete, Erwin; Villareal-Careaga, Jorge; Marfil, Alejandro; et al. (Frontiers in Pain Research, 2023)
Cluster headache (CH) is the most common and devastating autonomic headache with multiple and recent advances in treatment. However, it usually goes unrecognized and is found to have a delayed and inappropriate treatment. This paper aims to review the current therapeutic options for patients with CH. We conducted a narrative literature review on the treatments available for this condition using the American Academy of Neurology (AAN) classification of therapeutic evidence. We found effective and safe pharmacological and non-pharmacological therapies with heterogeneity of clinical trial designs for patients with CH, and they are divided into three phases, namely, transitional, acute, and preventive interventions. Prednisone (A) is the most studied treatment in the transitional phase; acute attacks are treated using triptans (A), oxygen (A), and non-invasive transcutaneous vagal nerve stimulation (A). Verapamil (A) and monoclonal antibodies (possible A) are considered the first options in preventive treatments, followed by multiple pharmacological and non-pharmacological options in prophylactic treatments. In conclusion, numerous effective and safe treatments are available in treating patients with episodic, chronic, and pharmacoresistant CH according to the clinical profile of each patient.